2015
DOI: 10.1097/qad.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete adherence among treatment-experienced adults on antiretroviral therapy in Tanzania, Uganda and Zambia

Abstract: Objectives To characterize antiretroviral therapy (ART) adherence across different programmes and examine the relationship between individual and programme characteristics and incomplete adherence among ART clients in sub-Saharan Africa. Design A cross-sectional study. Methods Systematically selected ART clients (≥18 years; on ART ≥6 months) attending 18 facilities in three countries (250 clients/facility) were interviewed. Client self-reports (3-day, 30-day, Case Index ≥48 consecutive hours of missed ART)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
85
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 58 publications
6
85
0
2
Order By: Relevance
“…Similar to other studies (2, 5, 6), unhealthy alcohol use was also associated with ART non-adherence in our multivariable model, although it did not reach statistical significance (Wald X 2 = 3.72; p-value = 0.054). This independent effect suggests that alcohol use may impact adherence in multiple ways, i.e.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to other studies (2, 5, 6), unhealthy alcohol use was also associated with ART non-adherence in our multivariable model, although it did not reach statistical significance (Wald X 2 = 3.72; p-value = 0.054). This independent effect suggests that alcohol use may impact adherence in multiple ways, i.e.…”
Section: Discussionsupporting
confidence: 86%
“…These findings are slightly better than the 29% failure we observed at 12 months. Notably, these outcomes are worse than recent reports from general adult ART clinics ranging from 9 to 16% virologic failure [31-33]. Other pregnancy-related studies have reported a high rate of loss from follow-up, but have not included virologic outcomes [14, 16, 34].…”
Section: Discussionmentioning
confidence: 97%
“…The amplitude of the effect of hazardous alcohol consumption on low adherence (adjusted OR 2.72) is higher to the one found in the literature: a meta-analysis published by Hendershot and colleagues in 2009 reported an OR of 1.82 [33]; Denison et al report a pooled OR of 1.87 [27], and Ayay et al 2.17 [30]. However, these studies did not examine for association with viral suppression.…”
Section: Discussionmentioning
confidence: 93%